(untitled) (CAHIERS MAGELLANES-NS, 2024)
Feminism in Indian English literature has been an important and evolving theme, reflecting the complex socio-cultural dynamics of Indian society. Indian women authors have addressed and critiqued gender issues, societal conventions, and the fight for women's rights through their literary works. This research paper gives a broader overview of how feminism has been represented and developed in Indian English literature and provides insight into the early voices and historical context in different timelines since the pre-independence era, the post-independence era, and also the contemporary voices and diverse perspectives. The themes and innovations are Modern Indian feminist literature frequently explores the intersection of gender with various social categories like caste, class, religion, and ethnicity, a concept known as intersectionality. This intersectional approach provides a more nuanced understanding of women's struggles and experiences. Indian literature has also reimagined the traditions of many contemporary Indian women writers who engage with traditional narratives and myths to offer feminist reinterpretations, challenging patriarchal norms while preserving cultural heritage. It also has a broader global perspective, and the global diaspora experience has also influenced feminist writings, bringing in perspectives from women who navigate both their traditional cultural contexts and the broader international landscape. The Narrative Style of Modern Indian Literature shows that the feminist writers experiment with many innovative narrative forms, blending traditional storytelling with contemporary styles to explore women's experiences in innovative ways. Therefore, this research paper evidently indicated that feminism in Indian English literature is a rich and evolving field, marked by diverse voices and perspectives. It depicts India's ongoing struggle for gender equality, as well as the complicated interplay between tradition and modernity. Indian women writers continue to question social norms, examine the complexity of female identity, and promote women's rights through their literature elaborating on feminism and its difficulties.